Implementation of Lean Management in School Administration Processes: An Approach to Efficiency and Work Effectiveness in the Technological Era - Yanuar, Muhammad; Nurabadi, Ahmad; Mustiningsih, Mustiningsih (Universitas Negeri Malang, 2024)
School administrative processes often face various challenges that hinder efficiency and effectiveness due to complex and manual procedures. These issues can negatively impact the management of quality education. The aim of this research is to analyze how lean management is applied in school administration and its effects on efficiency and work effectiveness, especially in today’s digital era. The method used in this study is a literature review by examining various relevant literature, journals, and articles. The results indicate that the application of lean management, supported by technology such as School Management Information Systems (SMIS), successfully reduced administrative processing time by up to 50%, improved data accuracy, and optimized the use of human resources. The conclusion of this study emphasizes that lean management can enhance school administrative performance, but its success greatly depends on effective change management and active staff involvement.